Ethylene induces endophyte bacteria to control early and late stage development in several plant species - Perry, Guenevere (PeerJ Preprints, 2016)
Plant growth promoting bacteria (PGPB) can modify plant growth and increase nutrient uptake. This study focuses on additional applications for PGPB in pre-harvest and post-harvest biotechnology.In this study a Bacillus sp. were exposed to urea, cobalt, and iron cofactors and induced with ethylene gas. The induced bacteria enhanced early stage development in cucumber plants. The bacetria increased seed germination by 25% and increased the number of blossoms per plant increased by over 50%. The induced Bacillus sp. controlled late stage development inseveral plants species. The bacteria delayed the effects of climacteric ripening in bananas and peaches. The PGPB may biosynthesize a compound that is released into the surrounding environment that affects early stage development and late stage development in several species of plants.
Keywords: Ethylene; Climacteric Ripening; PGPB; Cyanide; Plant Growth Promoting Bacteria; Crop Yield; Germination; monooxygenase; Indole-3-Acetic Acid; Post-Harvest Biotechnology